Potential phytate-degrading enzyme producing bacteria isolated from Malaysian maize plantation - Meor Hussin, Anis Shobirin; Abd. El Aziem, Farouk; Greiner, Ralf (Academic Journals, 2009)
Phytases catalyze the hydrolysis of phosphomonoester bonds in phytate, thereby releasing lower forms of myo-inositol phosphates and inorganic phosphate. Phytase enzyme preparations have a wide range of applications in animal and human nutrition. The addition of phytate-degrading enzyme can improve the nutritional value of plant-based foods by enhancing protein digestibility and mineral availability through phytate hydrolysis during digestion in stomach or during food processing. 30 strains of potential phytate-degrading enzymes bacteria isolated from Malaysian maize plantation were cultivated in Luria Bertani (LB) and Luria Bertani + Rice Bran (LBRB) media for 5 days and were analyzed for phytase activity. The 6 strains with highest activity were chosen for species identification. Two set of broad-range 16S rRNA PCR primers were used for genotypic identification. ASUIA279 was the strain that had has the highest phytase activity in LBRB followed by ASUIA271, ASUIA138, ASUIA260, ASUIA243 and ASUIA30. The genotypic technique revealed Pantoea stewartii ASUIA271, Enterobacter sakazakiiASUIA279, Bacillus cereus ASUIA260, Bacillus subtilis ASUIA243, P. stewartiiASUIA138 and B. cereus ASUIA30.